Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd000254.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamin and mineral supplements for slowing the progression of age-related macular degeneration

Abstract: Antioxidant vitamin and mineral supplements for slowing the progression of age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 70 publications
1
107
0
2
Order By: Relevance
“…The panel also notes that supplement use is not recommended for most survivors, except in instances of documented deficiencies (eg, survivors of gastric cancer), inadequate diet, or comorbid indications (eg, osteoporosis, 50 ophthalmologic disorders, 51 cirrhosis 52,53 ). Survivors should be advised that taking vitamin supplements does not replace the need for adhering to a healthy diet.…”
Section: Supplement Use In Survivorsmentioning
confidence: 99%
“…The panel also notes that supplement use is not recommended for most survivors, except in instances of documented deficiencies (eg, survivors of gastric cancer), inadequate diet, or comorbid indications (eg, osteoporosis, 50 ophthalmologic disorders, 51 cirrhosis 52,53 ). Survivors should be advised that taking vitamin supplements does not replace the need for adhering to a healthy diet.…”
Section: Supplement Use In Survivorsmentioning
confidence: 99%
“…It has been shown that people with drusen who take antioxidant supplementation are less likely to lose 15 or more letters of visual acuity over the follow-up (AREDS 2001), even though this benefit was considered modest in people with moderate to severe signs of the disease (Evans 2012). Antioxidants have not been shown beneficial in the primary prevention of AMD (Chong 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane meta-analysis performed on four large, high-quality-randomized clinical trials involving a total of 65,250 participants, without signs of AMD at baseline showed no efect of antioxidant therapy for preventing the onset of retinal degeneration per se [59]. Another Cochrane review meta-analysis [60] involving data from 13 randomized clinical trials, including two large trials, the AREDS1/2 and the Vitamin E Intervention in Cataract and Age-Related Maculopathy study, and 11 smaller (20-400 participants) randomized trials were performed to decide whether antioxidants can slow progression of retinal damage in patients with established AMD. The AREDS1/2 shows that long-term, high-dose supplementation with vitamin E (400 IU), vitamin C (500 mg), beta-carotene (15 mg), zinc (80 mg), and copper (2 mg) reduced the risk of progression to geographic atrophy AMD by 8% in only a subgroup of patients with intermediate AMD at baseline.…”
Section: Phototoxicitymentioning
confidence: 99%